2005
DOI: 10.1111/j.1083-6101.2005.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Online Communities: Design, Theory, and Practice

Abstract: This special thematic section of the Journal of Computer‐Mediated Communication brings together nine articles that provide a rich composite of the current research in online communities. The articles cover a range of topics, methodologies, theories and practices. Indirectly they all speak to design since they aim to extend our understanding of the field. The variety shown in these articles illustrates how broad the definition is of this rapidly growing field known as ‘online communities.’

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(138 citation statements)
references
References 10 publications
2
125
0
11
Order By: Relevance
“…Σύμφωνα με την Preece συνήθως ξεκινούν από κοινότητες στις οποίες τα μέλη έχουν φυσική επαφή. Στη συνέχεια ένα μέρος ή το σύνολο μεταφέρεται στο Διαδίκτυο, όπου αναπτύσσει μια Διαδικτυακή Κοινότητα ή αντιστρόφως τα μέλη μιας δικτυακής κοινότητας επιδιώκουν να έχουν φυσική παρουσία και να συναντηθούν πρόσωπο με πρόσωπο (Preece, 2000). Οι Διαδικτυακές (Εικονικές) Κοινότητες έχουν αποτελέσει ένα αντικείμενο ιδιαίτερου ενδιαφέροντος για τους εκπαιδευτικούς κύκλους, ιδιαίτερα στους λιγότερο th International Conference in Open & Distance Learning -November 2013, Athens, Greece -PROCEEDINGS Volume 2 -Section A: theoretical papers, original research and scientific articles 94 παραδοσιακούς τομείς, όπως η Τηλεκπαίδευση, οι Κοινότητες Μάθησης, η Δια βίου μάθηση, και η συνεχιζόμενη επαγγελματική ανάπτυξη (Goodfellow, 2003).…”
Section: διαδικτυακές (εικονικές) κοινότητεςunclassified
See 1 more Smart Citation
“…Σύμφωνα με την Preece συνήθως ξεκινούν από κοινότητες στις οποίες τα μέλη έχουν φυσική επαφή. Στη συνέχεια ένα μέρος ή το σύνολο μεταφέρεται στο Διαδίκτυο, όπου αναπτύσσει μια Διαδικτυακή Κοινότητα ή αντιστρόφως τα μέλη μιας δικτυακής κοινότητας επιδιώκουν να έχουν φυσική παρουσία και να συναντηθούν πρόσωπο με πρόσωπο (Preece, 2000). Οι Διαδικτυακές (Εικονικές) Κοινότητες έχουν αποτελέσει ένα αντικείμενο ιδιαίτερου ενδιαφέροντος για τους εκπαιδευτικούς κύκλους, ιδιαίτερα στους λιγότερο th International Conference in Open & Distance Learning -November 2013, Athens, Greece -PROCEEDINGS Volume 2 -Section A: theoretical papers, original research and scientific articles 94 παραδοσιακούς τομείς, όπως η Τηλεκπαίδευση, οι Κοινότητες Μάθησης, η Δια βίου μάθηση, και η συνεχιζόμενη επαγγελματική ανάπτυξη (Goodfellow, 2003).…”
Section: διαδικτυακές (εικονικές) κοινότητεςunclassified
“…Όταν μια διαδικτυακή κοινότητα έχει ως στόχο την παραγωγή γνώσης αλλά και την ανταλλαγή εμπειριών και καλών πρακτικών μεταξύ των μελών της, οπότε επιτελεί και τη λειτουργία της Κοινότητας Μάθησης, τότε λέγεται Ηλεκτρονική (ή Εικονική ή Διαδικτυακή) Μαθησιακή Κοινότητα ή Κοινότητα Μάθησης (Virtual Learning Community) (Αποστολάκης κ.α., 2008). Η Preece (2000) αναφέρει επίσης πως μια Δ.Κ.Μ. συγκροτείται από μια ομάδα ατόμων, τα οποία αλληλεπιδρούν κοινωνικά και επιδιώκουν να ικανοποιήσουν τις ιδιαίτερες ανάγκες τους, ή αναλαμβάνουν και υποδύονται ειδικούς ρόλους (ηγετικούς, διαμεσολαβητικούς), εμφανίζει έναν κοινό σκοπό (κοινά ενδιαφέροντα και διακριτές ανάγκες, όπως ανταλλαγή πληροφοριών ή παροχή υπηρεσιών), ο οποίος αποτελεί το λόγο ύπαρξης της κοινότητας, παρουσιάζει συγκεκριμένες πολιτικές λειτουργίας, η οποία χαρακτηρίζεται από κανόνες, πρωτοκόλλα συμπεριφοράς και επικοινωνίας που καθορίζουν τις αλληλεπιδράσεις μεταξύ των μελών, υποστηρίζεται από κατάλληλες ψηφιακές τεχνολογίες, οι οποίες διευκολύνουν και κυρίως προάγουν την κοινωνική αλληλεπίδραση.…”
Section: διαδικτυακές (εικονικές) κοινότητεςunclassified
“…In the following, we will further develop our theory of the "social scaffolding" of online communities and relate the fluidity/stability states to "shades" of reciprocity in online communities. Although other social mechanisms may be meaningful in that respect (e.g., homophily or preferential attachment), reciprocity is most crucial in knowledge-intensive online communities as it is the antecedent of sustained knowledge sharing (Chiu et al, 2006b;Faraj & Johnson, 2011;Preece & Maloney-Krichmar, 2005;Wasko & Faraj, 2005;Wiertz & de Ruyter, 2007). Based on social exchange theory (Blau, 1964), reciprocity entails that action may be reciprocated at some point in the future.…”
Section: Reciprocity and The Social Scaffolding Of Online Communitiesmentioning
confidence: 99%
“…Reciprocity has been widely discussed as a crucial social exchange mechanism in knowledge-intensive online communities (Chiu, Hsu, & Wang, 2006b;Faraj & Johnson, 2011;Preece & Maloney-Krichmar, 2005;Wasko & Faraj, 2005;Wiertz & de Ruyter, 2007). We propose to take a more fine-grained approach toward reciprocity and differentiate between sharing, support and sociality.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that virtual ethnography is an obvious candidate for developing a broad understanding of online behaviour within particular contexts (Preece and Maloney-Krichmar, 2005), some critics suggested that the representativeness of the findings is questionable and the study of online data alone is probably insufficient to understand how people use things they have read or said in their offline lives. For example, Bruckman argues:…”
Section: Representativenessmentioning
confidence: 99%